Penerapan Model Pembelajaran Blended-Problem Solving melalui Aplikasi Moodle untuk Meningkatkan Kemampuan Berpikir Kreatif Kelas XI IPA 4 SMA N 3 Surakata Tahun Pelajaran 2012/2013 - Vebriana Irandasari K W; Riezky Maya Probosari; Suciati Sudarisman (BIO-PEDAGOGI, 2014)
This study is aimed to improve creative thinking ability of XI IPA4 class of SMA N 3 Surakarta through the implementation of Blended-Problem Solving through moodle application. This research was a classroom action research held in 3 cycles, each cycle includes four stages: planning, action, observation, and reflection. The subject of this research is the students of XI IPA4 class at SMA N 3 Surakarta in academic year of 2012/2013. The data is obtained through the test (essay test) and non-test (observation, interviews and questionnaires). The data is analyzed with descriptive analytical techniques and validated by triangulation techniques. The results showed that students creative thinking ability is increased in Pre-cycle, Cycle I, Cycle II and Cycle III. Creative thinking consist of four aspects are fluency, flexibility, originality and elaboration. Fluency aspect has increased was 52,5%, flexibility aspect was 54,17%, the originality aspect was 61,66% and elaboration aspect was 55,83%. The research conclouded that the implementation of Blended-Problem Solving through moodle application can improve creative thinking ability of XI IPA4 class at SMA N 3 Surakarta in academic year of 2012/2013. Key Words: Blended-Problem Solving, Moodle, Creative Thinking